Immune and stem cell compartments of acetabular and femoral bone marrow in hip osteoarthritis patients. Issue 8 (August 2022) - Trivanovic, D.; Harder, J.; Leucht, M.; Kreuzahler, T.; Schlierf, B.; Holzapfel, B.M.; Rudert, M.; Jakob, F.; Herrmann, M.
Summary: Objective: Hip osteoarthritis (OA) affects all components of the osteochondral unit, leading to bone marrow (BM) lesions, and unknown consequences on BM cell functionality. We analyzed the cellular composition in OA-affected acetabula compared to proximal femur shafts obtained of hip OA patients to reveal yet not explored immune and stem cell compartments. Design: Combining flow cytometry, cellular assays and transcription analyses, we performed extensive ex vivo phenotyping of acetabular BM cells from 18 hip OA patients, comparing them with their counterparts from patient-matched femoral shaft BM samples. Findings were related to differences in skeletal sites and age. Results: Acetabular BM had a greater frequency of T-lymphocytes, non-hematopoietic cells and colony-forming units fibroblastic potential than femoral BM. The incidence of acetabular CD45 + CD3 + T-lymphocytes increased (95% CI: 0.1770 to 0.0.8416), while clonogenic hematopoietic progenitors declined (95% CI: −0.9023 to −0.2399) with age of patients. On the other side, in femoral BM, we observed higher B-lymphocyte, myeloid and erythroid cell frequencies. Acetabular mesenchymal stromal cells (MSCs) showed a senescent profile associated with the expression of survival and inflammation-related genes. Efficient osteogenic and chondrogenic differentiation was detected in acetabular MSCs, while adipogenesis was more pronounced in their femoral counterparts. Conclusion: Our results suggest that distinctions in BM cellular compartments and MSCs may be due to the influence of the OA-stressed microenvironment, but also acetabular vs femoral shaft-specific peculiarities cannot be excluded. These results bring new knowledge on acetabular BM cell populations and may be addressed as novel pathogenic mechanisms and therapeutic targets in OA.